Method for improving quality of semi-hydrated phosphogypsum

By adding inhibitors to semi-hydrophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophor

CN119797786APending Publication Date: 2025-04-11GUIZHOU CHANHEN CHEM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510234955.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-28
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Semi-hydrophosphorus gypsum has the disadvantages of fast coagulation and hardening and large water demand for products. It also contains moisture, which leads to agglomeration during the production process, limits its direct utilization and increases the energy consumption and cost of resource utilization.

Method used

Steady-state phosphophosphorus gypsum is prepared by mixing semi-hydrophosphorus with inhibitors such as sodium tripolyphosphate and/or sodium pyrophosphorus, and pulping and wet grinding to increase the specific surface area, reduce the water demand, and increase the absolute dry compressive strength.

Benefits of technology

Long-term phase steady-state storage and transportation of semi-hydrophorophor gypsum has been realized, which reduces the water demand for products, increases the absolute dry compressive strength, reduces energy consumption and costs, and broadens its utilization areas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005292502550000071
    Figure BDA0005292502550000071
Patent Text Reader

Abstract

The invention belongs to the field of chemical engineering, and particularly relates to a semi-hydrated phosphogypsum upgrading method which comprises the following steps: a) mixing a semi-hydrated phosphogypsum raw material with an inhibitor to obtain steady-state semi-hydrated phosphogypsum; in the step a), the inhibitor is sodium tripolyphosphate and / or sodium pyrophosphate; b) pulping the steady-state semi-hydrated phosphogypsum to obtain phosphogypsum slurry; then carrying out wet grinding on the phosphogypsum slurry to obtain wet grinding slurry; in the step b), the wet grinding time is 15 to 30 minutes; and c) carrying out solid-liquid separation on the wet abrasive slurry to obtain the upgraded semi-hydrated phosphogypsum. According to the technical scheme provided by the invention, the specific inhibitor is added into the semi-hydrated ardealite, so that the gelation activity of the semi-hydrated ardealite is inhibited, and the semi-hydrated ardealite can be in a phase steady state for a long time; on the basis, the steady-state semi-hydrated phosphogypsum is subjected to wet grinding, so that the specific surface area of the phosphogypsum is increased, the water demand of the semi-hydrated phosphogypsum product is reduced, and the absolute dry compressive strength of the semi-hydrated phosphogypsum product is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of chemical industry, and in particular relates to a method for improving the quality of hemihydrate phosphogypsum. Background Art

[0002] Phosphogypsum is a byproduct of the phosphate fertilizer and phosphoric acid industries. Every ton of phosphoric acid produced produces 4.5-5.0 tons of phosphogypsum. Currently, the annual output and accumulated stockpiles of phosphogypsum are huge, causing pollution and safety hazards to the ecological environment. Therefore, the resource utilization of phosphogypsum has become a problem that needs to be solved urgently for the sustainable development of phosphorus chemical enterprises.

[0003] From the perspective of wet phosphoric acid production process, the semi-hydrate phosphoric acid process has the advantages of low energy consumption and high output phosphoric acid concentration. The transition from dihydrate process to semi-hydrate process is the development trend of phosphorus chemical industry in the future. The main component of the phosphogypsum produced by the semi-hydrate phosphoric acid process is hemihydrate calcium sulfate (CaSO4·0.5H2O), which belongs to the category of a-hemihydrate calcium sulfate and has potential gelling activity. The gelling reaction of hemihydrate phosphogypsum is as follows:

[0004] CaSO4·0.5H2O+1.5H2O→CaSO4·2H2O.

[0005] However, the semi-hydrated phosphogypsum cementitious material has the disadvantages of fast coagulation and hardening, and high water requirement for the finished product. In addition, the phosphogypsum produced as a by-product of the wet phosphoric acid process contains a certain amount of water, which causes the semi-hydrated phosphogypsum produced to be converted into blocks and accompanied by agglomeration. Therefore, the direct utilization of the original semi-hydrated phosphogypsum is limited, and it needs to be dried to remove free water before use. For the above reasons, the utilization value of semi-hydrated phosphogypsum is low, and the energy consumption and cost of resource utilization are high. Summary of the invention

[0006] In view of this, the object of the present invention is to provide a method for improving the quality of hemihydrate phosphogypsum, which can produce high-quality stable hemihydrate phosphogypsum that is easy to transport, store, and directly use, thereby improving the resource utilization value of the hemihydrate phosphogypsum.

[0007] The present invention provides a method for improving the quality of hemihydrate phosphogypsum, comprising the following steps:

[0008] a) mixing a semi-hydrated phosphogypsum raw material with an inhibitor to obtain a stable semi-hydrated phosphogypsum;

[0009] In step a), the inhibitor is sodium tripolyphosphate and / or sodium pyrophosphate;

[0010] b) slurrying the stable hemihydrate phosphogypsum to obtain phosphogypsum slurry; and then wet-grinding the phosphogypsum slurry to obtain wet-grinded slurry;

[0011] In step b), the wet grinding time is 15 to 30 minutes;

[0012] c) performing solid-liquid separation on the wet grinding slurry to obtain upgraded hemihydrate phosphogypsum.

[0013] Preferably, in step a), the free water content of the semi-hydrated phosphogypsum raw material is 15-25wt%, and the crystallization water content is 6-7.5wt%.

[0014] Preferably, in step a), the specific surface area of ​​the hemihydrate phosphogypsum raw material is 60 to 120 m 2 / kg.

[0015] Preferably, in step a), the mass ratio of the inhibitor to the hemihydrate phosphogypsum raw material on a dry basis is (0.02-0.2):100.

[0016] Preferably, in step a), the mass ratio of the inhibitor to the hemihydrate phosphogypsum raw material on a dry basis is (0.05-0.15):100.

[0017] Preferably, in step b), the solid-liquid mass ratio of the phosphogypsum slurry is 1:(0.8-1).

[0018] Preferably, in step b), the mass ratio of balls to materials in wet grinding is 1:(5-10).

[0019] Preferably, in step b), the wet grinding time is 15 to 25 minutes.

[0020] Preferably, in step c), the free water content of the upgraded hemihydrate phosphogypsum is 12-22 wt%, the crystal water content is 6-7.5 wt%, and the specific surface area is 300-400 m 2 / kg.

[0021] Preferably, the method further comprises the following step: returning the liquid produced by the solid-liquid separation in step c) to step b) for pulping.

[0022] Compared with the prior art, the present invention provides a method for improving the quality of hemihydrate phosphogypsum, comprising the following steps: a) mixing the hemihydrate phosphogypsum raw material with an inhibitor to obtain stable hemihydrate phosphogypsum; in step a), the inhibitor is sodium tripolyphosphate and / or sodium pyrophosphate; b) pulping the stable hemihydrate phosphogypsum to obtain phosphogypsum slurry; then wet grinding the phosphogypsum slurry to obtain wet grinding slurry; in step b), the wet grinding time is 15 to 30 minutes; c) performing solid-liquid separation on the wet grinding slurry to obtain improved hemihydrate phosphogypsum. The technical solution provided by the present invention suppresses the gelling activity of the hemihydrate phosphogypsum by adding a specific inhibitor to the hemihydrate phosphogypsum, so that the hemihydrate phosphogypsum can be in a phase-stable state for a long time; on this basis, by wet grinding the stable hemihydrate phosphogypsum, the specific surface area of ​​the phosphogypsum is increased, the water demand of the hemihydrate phosphogypsum products is reduced, and the absolute dry compressive strength of the hemihydrate phosphogypsum products is improved. More specifically, the technical solution of the present invention has the following technical advantages:

[0023] (1) Since hemihydrate phosphogypsum is in a metastable state, it absorbs water and transforms into dihydrate gypsum. Therefore, the storage and transportation of hemihydrate phosphogypsum requires drying to remove free water and keep it in a dry environment. The technical solution of the present invention can inhibit the gelling activity of hemihydrate phosphogypsum, so that the hemihydrate phosphogypsum is in a phase-stable state for a long time, which is convenient for transportation and long-term storage.

[0024] (2) Hemihydrate phosphogypsum produced by hemihydrate wet phosphoric acid has high water requirement and poor strength as a product. The technical solution of the present invention increases the specific surface area of ​​hemihydrate phosphogypsum by wet grinding, improves the particle size distribution, reduces the water requirement of gypsum products, and improves the strength.

[0025] (3) In the traditional process, the semi-hydrated gypsum produced by semi-aqueous wet phosphoric acid contains a certain amount of water. Wet grinding will cause the gypsum to hydrate and harden, damaging the mill. Therefore, the semi-hydrated phosphogypsum needs to be dried before modified ball milling. The technical solution of the present invention suppresses the gelling activity of the semi-hydrated gypsum in a steady state, directly wet grinds to improve the quality of the semi-hydrated phosphogypsum, reduces the gypsum drying process, reduces energy consumption, and realizes the direct upgrading of the semi-hydrated phosphogypsum produced by the semi-aqueous wet phosphoric acid to make a high-quality cementitious material. DETAILED DESCRIPTION

[0026] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] The present invention provides a method for improving the quality of hemihydrate phosphogypsum, comprising the following steps:

[0028] a) mixing a semi-hydrated phosphogypsum raw material with an inhibitor to obtain a stable semi-hydrated phosphogypsum;

[0029] b) slurrying the stable hemihydrate phosphogypsum to obtain phosphogypsum slurry; and then wet-grinding the phosphogypsum slurry to obtain wet-grinded slurry;

[0030] c) performing solid-liquid separation on the wet grinding slurry to obtain upgraded hemihydrate phosphogypsum.

[0031] In the quality improvement method provided by the present invention, in step a), the semi-hydrated phosphogypsum raw material is semi-hydrated phosphogypsum produced by a semi-hydrated wet-process phosphoric acid device; the free water content of the semi-hydrated phosphogypsum raw material is preferably 15-25wt%, specifically 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt%, 21wt%, 21.4wt%, 22wt%, 23wt%, 24wt% or 25wt%; the structure of the semi-hydrated phosphogypsum raw material is preferably 15-25wt%, specifically 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt%, 21.4wt%, 22wt%, 23wt%, 24wt% or 25wt%; The crystal water content is preferably 6-7.5wt%, specifically 6wt%, 6.1wt%, 6.2wt%, 6.3wt%, 6.4wt%, 6.5wt%, 6.6wt%, 6.62wt%, 6.7wt%, 6.8wt%, 6.9wt%, 7wt%, 7.1wt%, 7.2wt%, 7.3wt%, 7.4wt% or 7.5wt%; the specific surface area of ​​the hemihydrate phosphogypsum raw material is preferably 60-120m 2 / kg, specifically 60m 2 / kg, 65m 2 / kg, 70m 2 / kg, 75m 2 / kg, 80m 2 / kg, 85m 2 / kg, 90m 2 / kg, 95m 2 / kg、100m 2 / kg, 105m 2 / kg, 110m 2 / kg, 112m 2 / kg, 115m 2 / kg or 120m 2 In the present invention, the crystal water content of the hemihydrate phosphogypsum raw material can usually reach more than 10wt% after being stored for 2 hours, and the gypsum appears to be agglomerated.

[0032] In the quality improvement method provided by the present invention, in step a), the inhibitor is sodium tripolyphosphate and / or sodium pyrophosphate; the mass ratio of the inhibitor to the hemihydrate phosphogypsum raw material on a dry basis is preferably (0.02-0.2):100, more preferably (0.05-0.15):100, specifically 0.05:100, 0.06:100, 0.07:100, 0.08:100, 0.09:100, 0.1:100, 0.11:100, 0.12:100, 0.13:100, 0.14:100 or 0.15:100.

[0033] In the quality improvement method provided by the present invention, in step b), the solid-liquid mass ratio of the phosphogypsum slurry is preferably 1:(0.8-1), specifically 1:0.8, 1:0.81, 1:0.82, 1:0.83, 1:0.84, 1:0.85, 1:0.86, 1:0.87, 1:0.88, 1:0.89, 1:0.9, 1:0.91, 1:0.92, 1:0.93, 1:0.94, 1:0.95, 1:0.96, 1:0.97, 1:0.98, 1:0.99 or 1:1.

[0034] In the quality improvement method provided by the present invention, in step b), the mass ratio of the ball material in the wet grinding is preferably 1:(5-10), specifically 1:5, 1:5.5, 1:6, 1:6.5, 1:7, 1:7.5, 1:8, 1:8.5, 1:9, 1:9.5 or 1:10; the wet grinding time is 15-30 min, preferably 15-25 min, specifically 15 min, 16 min, 17 min, 18 min, 19 min, 20 min, 21 min, 22 min, 23 min, 24 min or 25 min.

[0035] In the upgrading method provided by the present invention, in step c), the free water content of the upgraded hemihydrate phosphogypsum is preferably 12-22wt%, specifically 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt%, 21wt% or 22wt%; the crystallization water content of the upgraded hemihydrate phosphogypsum is preferably 6-7.5wt%, specifically 6wt%, 6.1wt%, 6.2wt%, 6.3wt%, 6.4wt%, 6.5wt%, 6.6wt%, 6.62wt%, 6.7wt%, 6.8wt%, 6.9wt%, 7wt%, 7.1wt%, 7.2wt%, 7.3wt%, 7.4wt% or 7.5wt%; the specific surface area of ​​the upgraded hemihydrate phosphogypsum is preferably 300-400m 2 / kg, specifically 300m 2 / kg、310m 2 / kg, 320m 2 / kg, 330m 2 / kg, 340m 2 / kg、350m 2 / kg, 360m 2 / kg, 370m 2 / kg, 380m 2 / kg, 390m 2 / kg or 400m 2 / kg; the storage time of the upgraded hemihydrate phosphogypsum when the crystal water content is stable at 6.0-7.5wt% is ≥72h.

[0036] In the quality improvement method provided by the present invention, it is preferred to further include the following step: returning the liquid produced by the solid-liquid separation in step c) to step b) for pulping.

[0037] The technical solution provided by the present invention suppresses the gelling activity of the semi-hydrated phosphogypsum by adding a specific inhibitor to the semi-hydrated phosphogypsum, so that the semi-hydrated phosphogypsum can be in a phase-stable state for a long time; on this basis, by wet grinding the stable semi-hydrated phosphogypsum, the specific surface area of ​​the phosphogypsum is increased, the water demand of the semi-hydrated phosphogypsum products is reduced, and the absolute dry compressive strength of the semi-hydrated phosphogypsum products is improved. More specifically, the technical solution of the present invention has the following advantages:

[0038] (1) The present invention adopts the steady-state inhibition of original hemihydrate phosphogypsum, and the hemihydrate phosphogypsum can be wet-ground without drying to improve the quality of phosphogypsum, with low energy consumption.

[0039] (2) The present invention directly upgrades the quality of the original phosphogypsum produced by semi-aqueous wet phosphoric acid and uses it as a high-quality cementitious material, thereby broadening the application field of the semi-hydrated phosphogypsum and making valuable use of the semi-hydrated phosphogypsum.

[0040] (3) The present invention undergoes steady-state suppression, so that the product can be transported and stored in a long-distance steady-state.

[0041] (4) The present invention has a simple operation process, causes little pollution to the production environment, and has a low cost for improving the quality of hemihydrate phosphogypsum.

[0042] For the purpose of greater clarity, the present invention is described in detail with reference to the following examples and comparative examples.

[0043] In the following embodiments and comparative examples of the present invention, the free water content of the semi-hydrated phosphogypsum produced by the semi-hydrated wet phosphoric acid device is 21.40wt%, the crystal water content is 6.62wt%, and the specific surface area is 112m 2 / kg, after 2h of storage, the crystallization water content reaches 10.17wt%, and the gypsum appears to be clumped into blocks.

[0044] Example 1

[0045] The semi-hydrated phosphogypsum from the semi-hydrated wet phosphoric acid device is added with an inhibitor (sodium tripolyphosphate) in an amount of semi-hydrated phosphogypsum (converted to dry basis): inhibitor mass ratio = 100:0.05, stirred and mixed evenly, and then slurried according to the solid-liquid mass ratio of 1:1. The slurry enters the wet mill with a ball mass ratio of 1:6 and is wet-milled for 20 minutes. The wet-milled slurry is solid-liquid separated to obtain the upgraded semi-hydrated phosphogypsum. There is no attachment on the surface of the wet mill after wet milling.

[0046] Example 2

[0047] The semi-hydrated phosphogypsum from the semi-hydrated wet phosphoric acid device is added with an inhibitor (sodium tripolyphosphate) in an amount of semi-hydrated phosphogypsum (converted to dry basis): inhibitor mass ratio = 100:0.1, stirred and mixed evenly, and then slurried according to the solid-liquid mass ratio of 1:1. The slurry enters the wet mill with a ball mass ratio of 1:6 and is wet-milled for 20 minutes. The wet-milled slurry is solid-liquid separated to obtain the upgraded semi-hydrated phosphogypsum. There is no attachment on the surface of the wet mill after wet milling.

[0048] Example 3

[0049] The semi-hydrated phosphogypsum from the semi-hydrated wet phosphoric acid device is added with an inhibitor (sodium tripolyphosphate) in an amount of semi-hydrated phosphogypsum (converted to dry basis): inhibitor mass ratio = 100:0.15, stirred and mixed evenly, and then slurried according to the solid-liquid mass ratio of 1:1. The slurry enters the wet mill with a ball mass ratio of 1:6 and is wet-milled for 20 minutes. The wet-milled slurry is solid-liquid separated to obtain the upgraded semi-hydrated phosphogypsum. There is no attachment on the surface of the wet mill after wet milling.

[0050] Example 4

[0051] The semi-hydrated phosphogypsum from the semi-hydrated wet phosphoric acid device is added with an inhibitor (sodium tripolyphosphate) in an amount of semi-hydrated phosphogypsum (converted to dry basis): inhibitor mass ratio = 100:0.1, stirred and mixed evenly, and then slurried according to the solid-liquid mass ratio of 1:1. The slurry enters the wet mill with a ball mass ratio of 1:6 and is wet-milled for 15 minutes. The wet-milled slurry is solid-liquid separated to obtain the upgraded semi-hydrated phosphogypsum. There is no attachment on the surface of the wet mill after wet milling.

[0052] Example 5

[0053] The semi-hydrated phosphogypsum from the semi-hydrated wet phosphoric acid device is added with an inhibitor (sodium tripolyphosphate) in an amount of semi-hydrated phosphogypsum (converted to dry basis): inhibitor mass ratio = 100:0.1, stirred and mixed evenly, and then slurried according to the solid-liquid mass ratio of 1:1. The slurry enters the wet mill with a ball mass ratio of 1:6 and is wet-milled for 25 minutes. The wet-milled slurry is solid-liquid separated to obtain the upgraded semi-hydrated phosphogypsum. There is no attachment on the surface of the wet mill after wet milling.

[0054] Comparative Example 1

[0055] The semi-hydrated phosphogypsum from the semi-hydrated wet phosphoric acid unit has no inhibitor (sodium tripolyphosphate) added. The semi-hydrated phosphogypsum is slurried according to a solid-liquid mass ratio of 1:1. The slurry enters the wet mill with a ball mass ratio of 1:6 and is wet-milled for 20 minutes. The wet-milled slurry is solid-liquid separated to obtain the upgraded semi-hydrated phosphogypsum. After wet milling, a small amount of gypsum agglomerates were found to be attached to the surface of the wet mill.

[0056] Comparative Example 2

[0057] The semi-hydrated phosphogypsum from the semi-hydrated wet phosphoric acid device is added with an inhibitor (sodium tripolyphosphate) in an amount of semi-hydrated phosphogypsum (converted to dry basis): inhibitor mass ratio = 100:0.1, stirred and mixed evenly, and then slurried according to the solid-liquid mass ratio of 1:1. The slurry enters the wet mill with a ball mass ratio of 1:6 and is wet-milled for 5 minutes. The wet-milled slurry is solid-liquid separated to obtain the upgraded semi-hydrated phosphogypsum. There is no attachment on the surface of the wet mill after wet milling.

[0058] Comparative Example 3

[0059] The semi-hydrated phosphogypsum from the semi-hydrated wet phosphoric acid device is added with an inhibitor (sodium tripolyphosphate) in an amount of semi-hydrated phosphogypsum (converted to dry basis): inhibitor mass ratio = 100:0.1, stirred and mixed evenly, and then slurried according to the solid-liquid mass ratio of 1:1. The slurry enters the wet mill with a ball mass ratio of 1:6 and is wet-milled for 35 minutes. The wet-milled slurry is solid-liquid separated to obtain the upgraded semi-hydrated phosphogypsum. There is no attachment on the surface of the wet mill after wet milling.

[0060] Performance Evaluation

[0061] The properties of the upgraded hemihydrate phosphogypsum of Examples 1 to 5 and Comparative Examples 1 to 3 were measured, and the results are shown in Table 1:

[0062] Table 1: Performance changes of hemihydrate phosphogypsum in examples and comparative examples

[0063]

[0064] Combined with the data in the above table, it can be seen that the hemihydrate phosphogypsum prepared by the wet phosphoric acid device has a small specific surface area, a high water requirement for gypsum products, and an absolute dry compressive strength of only 8.41MPa. Comparative Example 1, Examples 1 to 3 show that no inhibitor is added to the hemihydrate phosphogypsum in Comparative Example 1. Due to the metastable characteristics of hemihydrate phosphogypsum, the hemihydrate phosphogypsum is transformed from the hemihydrate phase to the dihydrate phase during the wet grinding process, accompanied by agglomeration, and the material adheres to the wet mill housing. The crystal water content increases to 9.75%, and the specific surface area is only increased to 208.62m 2 / kg, the absolute dry compressive strength of the product is only 5.73MPa. By adding the activity inhibitor, the activity of the hemihydrate gypsum is inhibited. During the steady-state wet grinding process, the hemihydrate phosphogypsum does not hydrate and harden, there is no attachment on the wet grinding machine shell, the crystal water of the gypsum after wet grinding is not converted, and the specific surface area is increased to about 370m 2 / kg, the water requirement of the product is reduced, and the absolute dry compressive strength is increased to about 27.0MPa. In addition, the inhibitor dosage can be adjusted according to the transportation and storage time required for the product to ensure the steady-state storage time, and the material has strong applicability.

[0065] Combined with the data in the above table, it can be seen that the addition of inhibitors to hemihydrate phosphogypsum can enable steady-state wet grinding of hemihydrate phosphogypsum. It can be seen from comparative examples 2 to 3 and examples 4 to 5 that there is no significant change in the crystal water content and steady-state storage time of hemihydrate phosphogypsum after wet grinding. As the ball milling time increases, the specific surface area of ​​hemihydrate phosphogypsum increases, the water demand of the product decreases first and then increases, and the absolute dry compressive strength of the product also shows a trend of increasing first and then decreasing. Wet grinding 5 minutes

[0066] The absolute dry strength is improved slightly after 35 minutes of wet grinding. The absolute dry compressive strength of the phosphogypsum is over-grinded and reduced. The steady-state wet grinding time of hemihydrate phosphogypsum is 15-25 minutes, which has a higher strength improvement effect.

[0067] In summary, compared with the original hemihydrate phosphogypsum, the absolute dry compressive strength of the hemihydrate phosphogypsum after steady-state wet grinding is increased from 8.41MPa to 27.0MPa, with a significant strength improvement. It can be used in the field of building materials. The controllability of the steady-state storage time and the large use radius of the hemihydrate phosphogypsum greatly increase the application value of the hemihydrate phosphogypsum.

[0068] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for improving the quality of hemihydrate phosphogypsum, characterized in that: The following steps are involved: a) mixing a semi-hydrated phosphogypsum raw material with an inhibitor to obtain a stable semi-hydrated phosphogypsum; In step a), the inhibitor is sodium tripolyphosphate and / or sodium pyrophosphate; b) slurrying the stable hemihydrate phosphogypsum to obtain phosphogypsum slurry; and then wet-grinding the phosphogypsum slurry to obtain wet-grinded slurry; In step b), the wet grinding time is 15 to 30 minutes; c) performing solid-liquid separation on the wet grinding slurry to obtain upgraded hemihydrate phosphogypsum.

2. The quality improvement method according to claim 1, characterized in that: In step a), the free water content of the semi-hydrated phosphogypsum raw material is 15-25wt%, and the crystal water content is 6-7.5wt%.

3. The quality improvement method according to claim 1, characterized in that: In step a), the specific surface area of ​​the hemihydrate phosphogypsum raw material is 60 to 120 m 2 / kg.

4. The quality improvement method according to claim 1, characterized in that: In step a), the mass ratio of the inhibitor to the hemihydrate phosphogypsum raw material on a dry basis is (0.02-0.2):

100.

5. The quality improvement method according to claim 4, characterized in that: In step a), the mass ratio of the inhibitor to the hemihydrate phosphogypsum raw material on a dry basis is (0.05-0.15):

100.

6. The quality improvement method according to claim 1, characterized in that: In step b), the solid-liquid mass ratio of the phosphogypsum slurry is 1:(0.8-1).

7. The quality improvement method according to claim 1, characterized in that: In step b), the mass ratio of the balls to materials in the wet grinding is 1:(5-10).

8. The quality improvement method according to claim 1, characterized in that: In step b), the wet grinding time is 15 to 25 minutes.

9. The quality improvement method according to claim 1, characterized in that: In step c), the free water content of the upgraded hemihydrate phosphogypsum is 12-22 wt%, the crystal water content is 6-7.5 wt%, and the specific surface area is 300-400 m 2 / kg.

10. The quality improvement method according to claim 1, characterized in that: The following steps are also included: The liquid produced by the solid-liquid separation in step c) is returned to step b) for pulping.